THE EFFECT OF GIVING PROPOLIS GEL 10% AND NEAR-INFRARED PHOTOTHERAPY ON POST-CURETTAGE WOUND HEALING - Erna Dwi Agustin; Suryono Suryono; Anggun Feranisa Akbar; Millania Murtikasari (Jurnal Medali, 2022)
Background: This study aims to specify the effect of topical administration of 10% propolis gel and near infrared phototherapy on post-curettage wound healing in terms of the thickness of the collagen fibers. Methods: This is an Experimental Laboratories using a Post Test Only Control Group design. The samples used were 36 male Sprague Dawley rats divided into 4 groups, namely: a group given 10% propolis gel, NIR, 10% propolis gel + NIR, and a control group. Preparations were made on the 3rd, 7th, 14th day, and stained using Sirius red paint. One Way Annova test with the Tukey HSD advanced test was used as data analysis. Results: The average amount of collagen fibers in the 10% + NIR propolis gel group had the highest results on days 3, 7, and 14. Based on the One Way Anova test, it was found that there was a difference between day 3 and day 7 p = 0.027, day 3 and day 14 p = 0.000 and day 7 and 14 p = 0.000. The test between the propolis and NIR groups had p> 0.05. Conclusion: There is an effect of using 10% propolis gel and near infrared on post-curettage wound healing seen from the increase in collagen fibers.